2008
DOI: 10.1029/2007tc002226
|View full text |Cite
|
Sign up to set email alerts
|

Temporal constraints and pulsed Late Cenozoic deformation during the structural disruption of the active Kashi foreland, northwest China

Abstract: In response to the ongoing Indo‐Asian collision, structural deformation has encroached into the Tian Shan foreland in western China since the early Miocene. In order to reconstruct a detailed history of foreland deformation along the southern margin of the Tian Shan, we have synthesized extensive mapping, analysis of seismic sections, magnetostratigraphy of the foreland fill and associated growth strata, apatite fission track dating, changes in sediment accumulation rates, and geodetic surveys of deformed fluv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
215
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(229 citation statements)
references
References 94 publications
14
215
0
Order By: Relevance
“…By comparing with geodetic data, Sobel et al (2006a) suggested this region experienced a complex shortening history in late Cenozoic. Four stages of tectonic deformation in the Atushi Basin in front of the SW Chinese Tian Shan at 20 ~ 25 Ma, ca.16.3 Ma, 4 ~ 13.5 Ma and after 4 Ma were constrained by magnetostratigraphic study, which lead to a total north south shortening of 10 -32 km (Heermance et al, 2008). The kinematic mechanism of the Atushi and Kashi folds were well constrained by Scharer et al (2004) and Chen et al (2007).…”
Section: Introductionmentioning
confidence: 94%
“…By comparing with geodetic data, Sobel et al (2006a) suggested this region experienced a complex shortening history in late Cenozoic. Four stages of tectonic deformation in the Atushi Basin in front of the SW Chinese Tian Shan at 20 ~ 25 Ma, ca.16.3 Ma, 4 ~ 13.5 Ma and after 4 Ma were constrained by magnetostratigraphic study, which lead to a total north south shortening of 10 -32 km (Heermance et al, 2008). The kinematic mechanism of the Atushi and Kashi folds were well constrained by Scharer et al (2004) and Chen et al (2007).…”
Section: Introductionmentioning
confidence: 94%
“…10e). The eastern part of the Qaidam Basin shows some evidence of tectonic activity at about ∼ 14.7 Ma events; the NW part after Zheng et al, 2000;Chen et al, 2002;Wang et al, 2003;Sun et al, 2004Sun et al, , 824 2005Sun et al, , 2007Sun et al, , 2009Charreau et al, 2005;2006;Huang et al, 2006;Heermance et al, 2007Heermance et al, , 2008825 Sun and Zhang, 2008;Tang et al, 2011 and; the NE part after Li et al, 1997;826 Song et al, 2001a, b;Zhao et al, 2001;Fang et al, 2003Fang et al, , 2005aZheng et al, 827 2006;Lin et al, 2010;Wang et al, 2010;and Wang et al, 2011a, b), and (g) the presumed 828 paleoaltimetry history after An et al (2006). 829 , tectonic uplift events in (e) the Qaidam Basin (rectangle showing the tectonic events; the western basin after Chang et al, 2012; the eastern basin after Fang et al, 2007, andXiong, 2009) and (f) the northern Tibetan Plateau (rectangles showing the tectonic events; the NW part after Zheng et al, 2000;Chen et al, 2002;Wang et al, 2003;Sun et al, 2004Sun et al, , 2007Sun et al, , 2009Charreau et al, 2005Charreau et al, , 2006Huang et al, 2006;Heermance et al, 2007Heermance et al, , 2008Tang et al, 2011, and; the NE part after ...…”
Section: Global Cooling and Tibetan Plateau Upliftmentioning
confidence: 99%
“…H. Song et al, 2001;Y. G. Song et al, 2001;Chen et al, 2002;Fang et al, 2003Fang et al, , 2005aWang et al, 2003;Sun et al, 2004Sun et al, , 2007Sun et al, , 2009Charreau et al, 2005Charreau et al, , 2006Huang et al, 2006;Heermance et al, 2007Heermance et al, , 2008Lin et al, 2010;Wang et al, 2010;W. T. Wang et al, 2011;Tang et al, 2011;Zhang and Sun, 2011;Nie et al, 2013) (Fig.…”
Section: Global Cooling and Tibetan Plateau Upliftmentioning
confidence: 99%
“…BaB.x-1 oil well registered the presence of several slices of the Choiyoi Group (Manceda et al, 1992). Comparable kinematic models, where superposition of basement-involved thrust sheets results in high elevations of basement rocks that produced deformation in the sedimentary cover, have been proposed in other fold and thrust belts in the Andes (e.g., Kley, 1996;McQuarrie et al, 2008) and elsewhere (e.g., Schönborn, 1999;Heermance et al, 2008).…”
Section: Thick-skinned Sector Of the Malargüe Ftbmentioning
confidence: 99%